(untitled) (Práxis Educativa, 2022)
This paper aims to reflect the changes in the Brazilian formal education system. As a starting point for the bibliographic analysis a quote from the book Education beyond capital, by the Hungarian philosopher István Mészáros, was used to describe an archaic educational model suggested by the English Enlightenment philosopher John Locke for the popular classes. In this way, it was discussed the uncritical educational processes, of alienating character, and critical educational processes, of formative character and their antagonism to vocational pedagogical models, modernized throughout history, but always within the same logic of reproducing inequalities of the capitalist system. In the end, the uncritical model and its unfolding are contextualized in Law no. 13.415, of February 16, 2017, of the Brazilian New High School, as well as the articulation of the main agents of interest in this law. Keywords: Ruling classes. Popular classes. New High School.